Growth and sustainability in post-Keynesian perspective: Some notes - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2023)
It can hardly be denied that perhaps the most serious challenge to mankind has not yet been addressed properly by post-Keynesianism: the over-stretching of our planetary boundaries. Most of the resources which we need to sustain our lives are non-renewable and, therefore, limited. And most of our production processes produce some kind of joint product (externality) like air, ground or water pollution which hold no value to the producer and instead harm the environment upon disposal. Consequently, the existence of mankind on this planet may be threatened when indispensable resources such as energy are running out and the environmental damage changes our living conditions in a way that mankind cannot survive.
Keywords: B59; E12; P18; Q50; 330; Ecological crisis; monetary production economy; zero growth; stagnation; growth imperative